DEVELOPMENT OF ISLAMIC EDUCATION TEACHING MATERIALS IN THE FIELD OF FIQH STUDIES IN PHASE B OF THE MERDEKA CURRICULUM AT SDN 0707 ALIAGA II HUTARAJA TINGGI DISTRICT PADANG LAWAS REGENCY - Fatimah Hasibuan; Zulhammi Zulhammi; Hamdan Hasibuan (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
Teachers are examples and facilitators for students in the teaching and learning process to achieve optimal competence. Teachers should be able to adjust learning resources that are useful and can support education and the goals and teaching and learning processes, both in the form of resource persons, textbooks, magazines, and newspapers. In addition, one of the efforts that can be made by a teacher in guiding or teaching students to understand the material well is by using teaching materials. This study aims to (1) produce PAI Fiqh teaching materials in Phase B, (2) produce a design for PAI Fiqh teaching materials in Phase B that are feasible in terms of validity, practicality, and effectiveness, The research method used is development research with the ADDIE model (analyze, design, development, implementation and evaluation). The subjects of the study were PAI teachers at SD Negeri 0909 Aliaga. Data collection in this study used an interview list, and a test instrument for the feasibility of the guide material, a test instrument for the feasibility of the guide display and a test instrument for the usability of the guide. The research data were analyzed using descriptive analysis, qualitative analysis and nonparametric analysis with the Kendall's Coefficient (W) statistical test and the Wilcoxon Rank Test. The results of the research show that: (1) the teaching materials used by PAI teachers are appropriate in terms of content and material, (2) the teaching materials can be used by PAI teachers and can be implemented well with students, (3) the level of appropriateness of the material is in the very feasible category with the percentage is 88.62%, and the display is in the very decent category with a percentage of 89.28%, and the level of use of guidance by PAI teachers is in the good category with a percentage of 74.66%. There was a significant increase in students' understanding results after PAI teachers used teaching materials that had been designed using the ADDIE model, so that these teaching materials could be said to be effective for PAI teachers to use in the teaching and learning process.